HUBUNGAN TINGKAT PENGETAHUAN DANDUKUNGAN KELUARGA TERHADAP KEPATUHAN DIET PASIEN DIABETES MELLITUS DI KLINIK BHAKTI HUSADA PURWAKARTA - Handayani, Handayani; Nuravianda L., Yanesti; Haryanto, Irwan (Sekolah Tinggi Ilmu Kesehatan Holistik, 2017)
Background: Diabetes mellitus (DM) is a state of chronic hyperglycemia accompanied by various disorders due to hormonal disturbances that cause a variety of chronic complications in the eyes, kidneys, nerves, and blood vessels. Family support is very important to motivate patients in performing the treatment of diabetes mellitus or diet. Objective: To examine the relationship of knowledge and family support for diet adherence DM outpatient clinic Bhakti Husada Purwakarta. Methods: This study is observational research with cross sectional design. Subjects were patients with DM Clinic Bhakti Husada Purwakarta amounting to 24 people. The data collected is the level of knowledge, family support, and dietary compliance. Data obtained through questionnaires. Analytical data using Chi-Square test. Results: The majority of respondents' knowledge level was classified as less (64.3%), and family support respondents to compliance in therapy of type 2 diabetes diet is good (50%). There is a relationship between knowledge and adherence diet DM patients (p = 0.008), but there is no relationship between family support compliance DM patients (p = 0.408). Conclusion: There is a relationship between knowledge with type 2 diabetes diet adherence.